Strategi Pembelajaran Berdiferensiasi Untuk Meningkatkan Kemampuan Literasi Membaca Pemahaman Siswa - Dwi Suratimah; Ngatmini Ngatmini (Institut Nalanda, 2023)
The purpose of this research is to describe the improvement of reading comprehension literacy skills through the application of differentiated learning strategies to students of the fifth grade of Primary School in the activities of learning to read and learn in the classroom. The method used is a qualitative approach with a descriptive method. Case study in 5th grade SDN Srondol Kulon 03 Semarang City. in limited face-to-face learning. The results of the research show that differentiated learning strategies are capable